The effects of an adequate thermal stimulation on the functional status of persons with deviations vegetovascular (Experimental biology, 2015)
Investigated visceral relationship vegetovascular persons with disabilities in the dynamics of work and thedevelopment of physical fatigue and their correction by adequate thermal stimulation. The objective of this research wasto clarify the influence of the temperature of adequate stimulation of thermosensitive areas of the skin on the autonomicparameters at dosed physical load and identify the most important ones for the correction of functional state of body andenhance human performance.
Keywords: heart rate variability; autonomic nervous system; heart rate; efficiency